Determining the Effects of Tryptophan Biomass on Growth Performance of 25- to 50-lb Nursery Pigs - M. R. Wensley; J. C. Woodworth; J. M. DeRouchey; S. S. Dritz; M. D. Tokach; R. D. Goodband; K. D. Haydon (Kansas Agricultural Experiment Station Research Reports, 2019)
A total of 315 barrows (DNA; 200 × 400; initially 24.9 lb) were used in a 21-d growth trial evaluating the effects of feeding TRP Pro (CJ America-Bio, Downers Grove, IL) as a source of Trp on nursery pig performance. Pigs were weaned at approximately 21 d of age, placed in pens based on initial body weight (BW), and fed common starter diets for 21 d. On d 21 after weaning, considered d 0 of the study, pigs were weighed and pens were allotted to 1 of 4 dietary treatments with 5 pigs per pen and 15 or 16 pens per treatment. Dietary treatments included a negative control (16% SID Trp:Lys ratio), positive control (21% SID Trp:Lys ratio from crystalline Trp), or diets containing Trp with biomass to provide 21 or 23.5% standardized ileal digestible (SID) Trp:Lys ratios (included at 0.104 or 0.156% of the diet, respectively). Diets were corn-soybean meal-based and contained 1.25% SID Lys with other amino acids set to meet or exceed NRC requirement estimates. The TRP Pro contained 60% Trp per the supplier’s specifications. Growth data were analyzed as a randomized complete block design using the PROC GLIMMIX procedure of SAS with pen as the experimental unit. Overall (d 0 to 21), pigs fed the 21% Trp:Lys ratio from crystalline Trp or Trp with biomass had increased (P<0.05) average daily gain (ADG) compared to pigs fed the negative control diet, with pigs fed the 23.5% Trp:Lys ratio with biomass intermediate. There was no evidence for difference in overall average daily feed intake (ADFI); however, pigs fed the 21% Trp:Lys ratio from Trp with biomass had improved (P<0.05) feed efficiency (F/G) compared to the negative control diet, with others intermediate. In conclusion, TRP Pro appears to be a suitable alternative to crystalline Trp in nursery pig diets but further evaluation at higher inclusion levels is needed.
Keywords: nursery pig; tryptophan; biomass